Does sandblasting improve bond strength in resin composite repair? - Roberto Zimmer; Aveline Ribeiro Mantelli; Kelin Montagna; Eduardo Galia Reston; Guilherme Anziliero Arossi (Elsevier, 2024)
There are many studies investigating the application of air abrasion as a surface treatment for resin-based composite (RBC) repair, some with conflicting results, which makes it difficult for the dentist to know whether to use it or not. The aim of this study is to produce an integrative literature review to identify the scientific evidence on the use of air abrasion for repairing direct RBC restorations. A PICO question was elaborated to guide the selection of literature in a database following the PRISMA statement. The keywords used in Medical Literature Analysis and Retrieval System Online (PubMed) and Service Scopus (SCOPUS) were "composite resin*'' AND ''air abrasion'' OR sandblasting AND repair* OR ''composite repair''. In Web of Science (WoS), the search strategy was ''composite resins'' AND ''air abrasion'' OR sandblasting AND ''composite repair''. Papers published in peer-reviewed journals since 2010, in English, and related to the aim of this study were the goal of this search. After applying inclusion and exclusion criteria to titles, abstracts, and full text, forty-nine scientific papers were selected for this study. This literature review focused on in vitro studies evaluating bond strength. The most common methodology found in the literature to evaluate bond strength in composite repair were shear and microshear bond strength tests (23 studies), as well as tensile and microtensile bond strength tests (24 studies). Several studies evidence air abrasion as an efficient mechanical surface treatment for composite repair, leading to a greater bond strength when compared to no preparation, diamond bur preparation alone, or distinct types of lasers.